Galectin-1 induces a tumor-associated macrophage phenotype and upregulates indoleamine 2,3-dioxygenase-1 - Asha M. Rudjord-Levann; Zilu Ye; Lise Hafkenscheid; Sabrina Horn; Renske Wiegertjes; Mathias A.I. Nielsen; Ming Song; Caroline B.K. Mathiesen; Jesse Stoop; Sean Stowell; Per Thor Straten; Hakon Leffler; et al. (iScience, 2023)
Summary: Galectins are a group of carbohydrate-binding proteins with a presumed immunomodulatory role and an elusive function on antigen-presenting cells. Here we analyzed the expression of galectin-1 and found upregulation of galectin-1 in the extracellular matrix across multiple tumors. Performing an in-depth and dynamic proteomic and phosphoproteomic analysis of human macrophages stimulated with galectin-1, we show that galectin-1 induces a tumor-associated macrophage phenotype with increased expression of key immune checkpoint protein programmed cell death 1 ligand 1 (PD-L1/CD274) and immunomodulator indoleamine 2,3-dioxygenase-1 (IDO1). Galectin-1 induced IDO1 and its active metabolite kynurenine in a dose-dependent manner through JAK/STAT signaling. In a 3D organotypic tissue model system equipped with genetically engineered tumorigenic epithelial cells, we analyzed the cellular source of galectin-1 in the extracellular matrix and found that galectin-1 is derived from epithelial and stromal cells. Our results highlight the potential of targeting galectin-1 in immunotherapeutic treatment of human cancers.